2008
DOI: 10.7863/jum.2008.27.1.109
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Findings in Fetal Cardiac Section Drawings

Abstract: Objective. The goal of this presentation is to review some of the common and rare fetal heart abnormalities and to provide an easy approach to these findings with the schematic drawings. Methods. Over the past 10 years, we collected cases in which the common views of the heart were abnormal and the differential diagnoses that existed for each. This presentation shows the normal sonographic sections and then variations of these sections and the associated anomalies. We used illustrative drawings to present thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Instead, some abnormal signs presenting at the standard cardiac views may provide some useful information, which may help the diagnosis of fetal PAPVC. Jeanty et al indicated the possibility of a LSVC or a VV for an additional vessel presenting on the left of the pulmonary artery at the 3VT view. We think it is useful for screening sonographers or echocardiographers to bear in mind such signs in standard cardiac views together with possible malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, some abnormal signs presenting at the standard cardiac views may provide some useful information, which may help the diagnosis of fetal PAPVC. Jeanty et al indicated the possibility of a LSVC or a VV for an additional vessel presenting on the left of the pulmonary artery at the 3VT view. We think it is useful for screening sonographers or echocardiographers to bear in mind such signs in standard cardiac views together with possible malformations.…”
Section: Discussionmentioning
confidence: 99%
“…The 3‐vessel view (3VV) and 3‐vessel and trachea view (3VT), lying in the same transverse plane orientation as the 4CV, have long been recognized as potentially important additions to the fetal cardiac screening evaluation . Importantly, the 3VV and 3VT have been found to improve detection of outflow tract abnormalities, abnormalities of the aortic arch, abnormalities of systemic veins, and even thymic abnormalities .…”
mentioning
confidence: 99%
“…7 The 3-vessel view (3VV) and 3-vessel and trachea view (3VT), lying in the same transverse plane orientation as the 4CV, have long been recognized as potentially important additions to the fetal cardiac screening evaluation. [8][9][10] Importantly, the 3VV and 3VT have been found to improve detection of outflow tract abnormalities, 8,[11][12][13] abnormalities of the aortic arch, [12][13][14][15] abnormalities of systemic veins, 16 and even thymic abnormalities. 17,18 The 3VV and 3VT should be considered complementary to the 4CV and left and right ventricular outflow tract views; a subtle abnormality in one view may be more apparent in another view.…”
mentioning
confidence: 99%